Penggunaan Metode Random Forest, Support Vector Machine dan Artificial Neural Networks dalam Prediksi Suhu Udara di Balikpapan - Erika Meinofelia; Mochamad Aryono Adhi; Achmad Fahruddin Rais; Djunaidi Djunaidi; Feddy Setio Pribadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aimed to compare the performance of three algorithmic models, namely Random Forest, Support Vector Machine (SVM), and Artificial Neural Networks (ANN), in predicting air temperature in Balikpapan. Changes in air temperature influenced by various climatic and geographical factors present a major challenge in urban planning; thus, accurate predictions are crucial to support sustainable and climate-adaptive city planning. The dataset used consists of observational data from the Balikpapan Meteorological Station, BMKG, over ten years, from January 2014 to December 2024. The models were evaluated using Mean Squared Error (MSE), Root Mean Squared Error (RMSE), and R Squared (R²) metrics. The results show that the SVM method produced an MAE of 0.17, RMSE of 0.21, and R² of 0.95, providing better predictions than ANN and Random Forest. In conclusion, SVM is an effective method for air temperature prediction in Balikpapan. Keywords: Artificial Neural Networks, Random Forest, Support Vector Machine, Machine Learning, Air Temperature Prediction